2019
DOI: 10.1186/s12969-019-0365-y
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-associated Hypogammaglobulinemia in pediatric patients with autoimmune diseases

Abstract: Background Despite the increased use of rituximab in treating pediatric patients with autoimmune diseases in the last decade, there are limited data on rituximab safety in those subjects who have a developing immune system. The objective of this study is to determine the prevalence of hypogammaglobulinemia in children with autoimmune disease receiving rituximab within the first three years of treatment in the pediatric rheumatology clinic at a tertiary care center. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 19 publications
1
53
1
2
Order By: Relevance
“…Short-and long-term effects of the most frequently used AIC treatments (steroids and rituximab) and supportive care measures (transfusions) are well established in various populations. 12,[34][35][36][37] Comparing our AIC cohort to controls, we found that iron overload and steroid-induced late effects including AVN and cataracts were more prevalent. This is likely attributed to the higher need of transfusion support leading to iron overload and prolonged courses of steroids to treat these AICs.…”
Section: Discussionmentioning
confidence: 81%
“…Short-and long-term effects of the most frequently used AIC treatments (steroids and rituximab) and supportive care measures (transfusions) are well established in various populations. 12,[34][35][36][37] Comparing our AIC cohort to controls, we found that iron overload and steroid-induced late effects including AVN and cataracts were more prevalent. This is likely attributed to the higher need of transfusion support leading to iron overload and prolonged courses of steroids to treat these AICs.…”
Section: Discussionmentioning
confidence: 81%
“…Another problem is that the use of TNF inhibitors to treat other rheumatic diseases, such as psoriatic arthritis, has precipitated the development of JDM [135], as well as inflammatory myopathies in adults [136,137]. immunoglobulin G (IgG) levels is advisable, especially in the first year of therapy, for there is a 30-50% prevalence of hypogammaglobulinemia; some patients require an immunoglobulin replacement therapy [138]. Rituximab has been used successfully to treat JDM patients who failed first-line therapy [139,140], [141].…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…Rituximab is the most commonly used biologic in the treatment of JDM (106). Serum immunoglobulin G (IgG) levels should be monitored; 30–50% of children may develop hypogammaglobinemia in the first year of therapy (112, 113). The child’s B cell response to rituximab can be evaluated by sequential CD19+ absolute counts (flow cytometry).…”
Section: Childhood and Adult Onset Dermatomyositis Have Differing Feamentioning
confidence: 99%